La mémoire et le double - Paré, François (CV Photo)

(untitled) (Les Productions Ciel variable, 2000)
This text, the product of parallel readings of Mercure, a novel by Amélie Nothomb, and L’avenir de la mémoire, an essay by Fernand Dumont, explores the tight links between identity, image, and memory. In Nothomb's novel, the main character is trapped by the absence of all representation: in this sense, deprivation of thought is a condition not of liberation but of imprisonment. Similarly, overshadowed communities try to represent themselves to themselves in the space of the image. It is the denial of their representation that establishes the limitations within which they evolve.